Vulvovaginal candidiasis among female patients attending the central STD Clinic Colombo, for the first time - Wijeratne, P.I (My University, 2008)
This study was a descriptive cross-sectional study on vulvovaginal candidiasis (VVC) among women attending the Central STD Clinic in Sri Lanka for the first time. This study involved 96 participants who visited the Central STD Clinic Colombo from January to March 2007, for the first time. Data was collected by using an interviewer-administered questionnaire and by taking two swabs from the lateral vaginal wall from each attendee during the speculum examination. From one swab, wet mount was prepared using 10percent KOH and other swab was used for culture. Isolates from women who were symptomatic with heavy growth in the culture were processed further, specification test. Antifungal susceptibility was done using the standard agar diffusion method developed by using Neo-sensitab antifungals and modified shadomy agar. The proportion of VVC among women attending the STD clinic for the first time is 8.33 percent. Symptoms and signs of VVC are not specific to diagnose VVC. Many of the isolates were Canadida albicans and the proportion of Candida tropicalis still remain low.